المراة الجزائرية في اهتمامات جمعية العلماء المسلمين الجزائريين - نادية لبقع; د/ فاطمة دجاج (جامعة عمار ثليجي الاغواط, 2024)
ملخص منذ ولوج المستعمر الفرنسي إلى الجزائر عمل على الإستحواذ على البلاد و الشعب عمل على تطبيق سياساته و إستراتيجياته خاصة على العنصر النسوي ، فاستخدم معه سياسته التغريبية و التنصيرية خاصة إنشاء مدارس فرنسية و معامل حرفية و ضمت فيها نساء أوروبيات عملن على استقطاب النساء الجزائريات و إغرائهنّ من أجل الانسياق معهن و تسهيل عملهن في التغلغل وسط العائلات الجزائرية - باعتبار أن المرأة المحرك الأولي للمجتمع، وهذا ما أدى إلى ظهور حركة اصلاحية واسعة في البلاد عملت على تسخير كل مجهوداتها من أجل تنقية المجتمع الجزائري مما علق به من مفاسد وبدع أحدثها المستدمر الفرنسي مركزة بذلك على المرأة وقضاياها الاجتماعية والثقافية لبعث النهضة والصحوة فيها، فقد شغلت المرأة حيزا واسعا في صحف جمعية العلماء المسلمين خاصة الشهاب والبصائر وتجلى إهتمامهم في مقالات وأدبيات نشرها علماء الجمعية أمثال البشير الابراهيمي، عبد الحميد بن باديس، الطيب العقبي، الأمين العمودي وغيرهم ممن وجهوا رسائلهم النهضوية في المجتمع ولم يكتفوا بعرض قضايا المرأة الدينية و الاجتماعية والثقافية التي تعكس مدى الانحراف الفكري و العقدي الذي طال عقيدة المرأة و تفكيرها، بل راحوا يبحثون عن الأسباب التي تقف وراءها و اقتراح بعض الحلول الممكنة لحل مثل هذه الظواهير السلبية، وذلك بمحاربة السياسات الفرنسية المضللة لعقول النساء، و الدعوة إلى تعليم المرأة تعليما صحيحا يحفظ لها دينها و قوميتها، وهذا الهدف الأسمى لجمعية العلماء المسلمين الجزائريين. Abstract : Since the French colonial entry into Algeria, they have worked on seizing the country and its people, implementing their policies and strategies, especially regarding the female element. They utilized their policy of westernization and Christianization, particularly by establishing French schools and vocational workshops that included European women. They aimed to attract Algerian women and entice them to align with them, facilitating their infiltration into Algerian families. Recognizing women as the primary drivers of society, this led to a widespread reform movement in the country. This movement aimed to harness all efforts to purify Algerian society from the vices and innovations introduced by the destructive French. It focused on women and their social and cultural issues to spark revival and awakening. Women occupied a prominent place in the newspapers of the Muslim Scholars Association, especially in "Ash-Shihab" and "Al-Basa'ir". Their interest manifested in articles and literary works published by scholars of the association such as Al-Bashir Al-Ibrahimi, Abdelhamid Ben Badis, At-Tayyib Al-Aqbi, Al-Amin Al-Umudi, and others who conveyed their reformist messages in society. They not only presented the religious, social, and cultural issues of women reflecting the extent of the intellectual and doctrinal deviation that affected women's creed and thinking but also sought the reasons behind it and proposed some possible solutions to address such negative phenomena. This involved combating the misleading French policies targeting women's minds and advocating for providing women with proper education that preserves their religion and nationality, which is the noblest goal of the Algerian Muslim Scholars Association الدراسة: